Characterization of the heparin-binding site of protein Z-dependent protease inhibitor - Yang, Likui (2012)
High molecular weight heparins promote the protein Z-dependent protease inhibitor (ZPI) inhibition of factors Xa (FXa) and XIa (FXIa) by a template mechanism. To map the heparin-binding site of ZPI, the role of basic residues of the D-helix (residues Lys-113, Lys-116, and Lys-125) in the interaction with heparin was evaluated by either substituting these residues with Ala (ZPI-3A) or replacing the D-helix with the corresponding loop of the non-heparin binding serpin α(1)-proteinase inhibitor (ZPI-D-helix(α1-PI)). Furthermore, both the C-helix (contains two basic residues Lys-104 and Arg-105) and D-helix of ZPI were substituted with the corresponding loops of α(1)-PI (ZPI-CD-helix(α1-PI)). All mutants exhibited near normal reactivity with FXa and FXIa in the absence of cofactors and in the presence of protein Z and membrane cofactors. By contrast, the mutants interacted with heparin with a lower affinity and the ~48-fold heparin-mediated enhancement in the rate of FXa inhibition by ZPI was reduced to ~30-fold for ZPI-3A, ~15-fold for ZPI-D-helix(α1-PI), and ~8-fold for ZPI-CD-helix(α1-PI). Consistent with a template mechanism for heparin cofactor action, ZPI-CD-helix(α1-PI) inhibition of a FXa mutant containing a mutation in the heparin-binding site (FXa-R240A) was minimally affected by heparin. A significant decrease (~2–5-fold) in the heparin template effect was also observed for the inhibition of FXIa by ZPI mutants. Interestingly, ZPI derivatives exhibited a markedly elevated stoichiometry of inhibition with FXIa in the absence of heparin. These results suggest that basic residues of both the C and D helices of ZPI interact with heparin to modulate the inhibitory function of the serpin.